Pepsinogen Serology and Gastritis OLGA Staging in Mucosal Atrophy Assessment: A Cross-Sectional Study Involving East China Endoscopy Population - Junjun Xia; Zhenzhen Liu; Kaiguang Zhang (Gastroenterology Research and Practice)
The histological gastric stage (OLGA) plays an important role in evaluating gastric atrophy, a symptom which suggests a risk of gastric cancer (GC). However, gastroscopy is an invasive examination, which has limited application in populations undergoing physical examination. Serum pepsinogen (PG) and gastin-17 (G-17) levels are noninvasive indexes which are recommended when screening for GC. We aim to explore the correlation between PG/G-17 and OLGA stage, in order to provide reliable indexes for GC screening. The study included 453 asymptomatic individuals from East China undergoing physical examination, who then underwent endoscopy including collection of biopsy samples. Assays for serum PG, G-17, and Helicobacter pylori (Hp) were performed. Atrophy of gastric mucosa was graded according to OLGA for each individual. 453 participants, average age 52.46±10.30 years, 253 male and 200 female, were included. In the asymptomatic physical examination population, serum PGI, PGII, and PGR levels decreased with increasing OLGA scores. PGI and PGR were inversely correlated with increasing OLGA stage in both Hp-positive and Hp-negative groups. The levels of serum PGI, PGII, and G-17 in the Hp-positive group were higher than those in the Hp-negative group; conversely, the PGR levels were lower. Furthermore, OLGA scores increased with age in the Hp-positive group. In conclusion, there is a significant correlation between OLGA stage and serum PG in populations from East China undergoing physical examination. Serum PG and G-17 combined with Hp test plays an important role in evaluating gastric atrophy.